José Gaos, Edmundo O’Gorman, Leopoldo Zea y el Seminario para el estudio del pensamiento en los países de lengua española - Valero Pie, Aurelia (El Colegio de México, A.C., 2014)
Knowing the origins of the history of ideas in Mexico involves remembering the names of José Gaos, Edmundo O’Gorman, and Leopoldo Zea, who, from different standpoints, set the discipline's theoretical and methodological foundations. Following the teachings of the eldest, and having as a background the Seminario para el estudio del pensamiento en los países de lengua española (Seminar for the Study of Thought in Spanish-Speaking Countries), the three held a long-standing dialogue, the implications of which for the history of ideas are the main focus of this paper.